2019
DOI: 10.1049/hve.2018.5067
|View full text |Cite
|
Sign up to set email alerts
|

Transformer components impact on compatibility of measured PDs: comparison of IEC60270 and RF methods

Abstract: Power transformer partial discharge signal measurement using Radio Frequency method has advantages over IEC 60270 'apparent charge' measurement method for online monitoring due to greater immunity against external interference. However, the lack of a well-defined calibration relationship between the two methods is main disadvantage of RF method. Simultaneous measurements, using these two methods, carried out on various transformer PD source models, in laboratory, to investigate main parameters that affect the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…v e, th n ε + α e n ⋅ μ ε ⋅ E n ε − ∑εγ Γ ⋅ n (17) The first term on the right-hand side of (16) and (17) refers to the changes in the number and energy of electrons caused by the disappearance/rebound of electrons on the wall due to thermal motion, where r e is the reflection coefficient. The value ranges from 0 to 1 and is set to 0 in this paper.…”
Section: Wall Boundary Conditionmentioning
confidence: 99%
See 1 more Smart Citation
“…v e, th n ε + α e n ⋅ μ ε ⋅ E n ε − ∑εγ Γ ⋅ n (17) The first term on the right-hand side of (16) and (17) refers to the changes in the number and energy of electrons caused by the disappearance/rebound of electrons on the wall due to thermal motion, where r e is the reflection coefficient. The value ranges from 0 to 1 and is set to 0 in this paper.…”
Section: Wall Boundary Conditionmentioning
confidence: 99%
“…Nowadays, needle-plate [16] and needle-bar [17] are two main electrode structures used to simulate surface discharge. The strong normal component of electric field with the needle-plate electrode structure can easily cause partial discharge in the dielectric, leading to the longitudinal breakdown of solid insulation.…”
Section: Electrode Structurementioning
confidence: 99%
“…Rahman concluded that the magnitude of the pulses depends on the shape of the electrode. Also, Firuzi et al investigated the corona, surface discharge in air and oil medium using radiofrequency and IEC60270 techniques, and concluded PD recorded by the surface discharge in the air had a higher amplitude than in oil [46]. As for the application, FOAS can be placed close to the transformer winding to detect the PD coming from that region, as a similar position as RTD or fiber optic based temperature sensor, which placed to detect winding temperature for the triggering an alarm or tripping the protection relay.…”
Section: B Test For Pd Measurementmentioning
confidence: 99%
“…Electromagnetic disturbance phenomena such as switch operation, lightning impact, short-circuit current, insulation breakdown, spark discharge, power frequency electric field, and power frequency magnetic field may affect secondary electronic equipment. Among them, the fault case of the signal acquisition unit on the secondary side of the electronic transformer under strong transient electromagnetic disturbance of the switch operation is the most prominent, and relevant accident cases are reported from time to time -165 [5][6][7][8]. Therefore, it is urgent to grasp the transient disturbance level of the signal acquisition port of the electronic transformer under the operation of the isolation switch to ensure safe and reliable operation of the smart substation.…”
Section: Introductionmentioning
confidence: 99%